Temporal Changes in Taxonomic and Functional Diversity of Fish Assemblages in the Upper Yangtze River After Impoundment of the Three Gorges Reservoir, China - Zhang, Chen; Liu, Fei; Liu, Huanzhang; Wang, Chunling; Lin, Pengcheng; Gao, Xin (Frontiers in Environmental Science, 2022)
Anthropogenic disturbance has become the primary driver that provokes loss of biodiversity. The temporal changes of community diversity and structure respond to persistent disturbance. In this study, we investigated the temporal changes of taxonomic and functional diversity of fish assemblages in different habitats (Three Gorges Reservoir (TGR), upstream of the TGR (UTGR), and tributary—Chishui River (CSR)) in the upper Yangtze basin after impoundment of the TGR from 2008 to 2015. The taxonomic and functional composition in fish assemblages significantly differed among these habitats. The taxonomic diversity presented the uptrend changes after impoundment, but downtrend in functional diversity. The directional change of species composition had a bigger slope in the TGR than the UTGR and CSR. Our results found that the impoundment imposed more effects on the TGR than the UTGR, but slightly affected the CSR. After impoundment, despite of uptrend of species richness in the upper Yangtze, fish biodiversity in the whole Yangtze decreased dramatically comparing with that before impoundment. However, species traits trend to homogenization. We inferred that niche and neutral processes could conjointly act on fish assemblage assembly processes after impoundment of the TGR, but the role of niche could be more dominant than neutral processes. In order to further protecting fish biodiversity in the Yangtze under background of the ten-years fishing ban, it is suggested to remove small dams in tributaries, to carry out releasing and ecological regulation, and to persist monitoring.